PERKARA FIKTIF POSITIF DAN PERMASALAHAN HUKUMNYA - Simanjuntak, Enrico (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2017)
Law of Administration (UUAP) has adopted a conception of Lex Silencio Positivo, a legal mechanism that requires the administering authority to respond or issue a decision/action brought before it within the limit of a certain time and if these preconditions are not met, the administering authority is deemed to have granted the application for the issuance of the decision/action it. As a new legal concept, rules of lex silentio positivo the realm of administrative law that Indonesia is known as â€œfictitious approvalâ€ or â€œtacit authorizationâ€ requires assessment, harmonization with the provisions of the previous law, namely the concept of fictitious negative decision. This paper intends to discuss some key notes concerning the conception of fictitious positive in Indonesia administrative law.Keywords: law of administration, fictitious approval, fictitious rejection